2021
DOI: 10.1002/tafs.10320
|View full text |Cite
|
Sign up to set email alerts
|

Invasive Lake Trout Reproduction in Yellowstone Lake under an Active Suppression Program

Abstract: In Yellowstone Lake, predation by invasive Lake Trout Salvelinus namaycush has caused significant abundance declines in native Yellowstone Cutthroat Trout Oncorhynchus clarkii bouvieri. Lake Trout suppression has been ongoing since 1995; assessment and simulation modeling are used to measure suppression effectiveness and guide efforts. Lake Trout reproduction demographics are linked to these modeling efforts via quantification of the population stock-recruitment relationship. To improve estimation of this rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…This extensive suppression effort has reduced adult lake trout abundance by >80% since 2012; however, recruitment of young lake trout remains high (Koel, Arnold, et al, 2020). The lake trout spawn from late September to early October (Heredia et al, 2021) at sites characterized primarily by cobble and bedrock substrate; confirmed lake trout spawning sites range in size from 0.3 to 2.0 ha and comprise 0.03% of the total area of Yellowstone Lake . To curtail lake trout recruitment and improve suppression efficiency, the NPS has developed a novel method that deposits carcasses directly on spawning areas in the littoral zone of the lake to induce decomposition and cause mortality in lake trout embryos via oxygen depletion (Poole et al, 2020;Thomas et al, 2019).…”
Section: Study Areamentioning
confidence: 99%
“…This extensive suppression effort has reduced adult lake trout abundance by >80% since 2012; however, recruitment of young lake trout remains high (Koel, Arnold, et al, 2020). The lake trout spawn from late September to early October (Heredia et al, 2021) at sites characterized primarily by cobble and bedrock substrate; confirmed lake trout spawning sites range in size from 0.3 to 2.0 ha and comprise 0.03% of the total area of Yellowstone Lake . To curtail lake trout recruitment and improve suppression efficiency, the NPS has developed a novel method that deposits carcasses directly on spawning areas in the littoral zone of the lake to induce decomposition and cause mortality in lake trout embryos via oxygen depletion (Poole et al, 2020;Thomas et al, 2019).…”
Section: Study Areamentioning
confidence: 99%